AplikasiI Klonosewandono Sebagai Bahan Ajar BIPA Pada Ketrampilan Membaca Tingkat Dasar - Ida Yeni Rahmawati; Siti Asiyah; Dyah Mustikasari (Universitas Muhammadiyah Ponorogo, 2020)
This study discusses the application of a BIPA teaching, especially in reading skills through an application. The purpose of this study is to explain the teaching materials presented in the Klonosewandono application at basic level BIPA teaching. The research method used is descriptive qualitative. The reference source used here is in the form of the BIPA AI handbook